Economic efficiency and prospects of introduction of biological methods of defence of plants are in the agricultural forming of the SouthKazakhstan area - Abylgazieva, Zh.; Sabyrova, M.; Dyuisembekova, G.; Uzbekova, R. (Journal of Economic Research & Business Administration, 2016)
This article analyzes the results of studies on the use of biological methods of plant protection against pests and diseases in the rural areas of South Kazakhstan region. Sound economic efficiency of use of biologi- cal agents and biological products in crop protection. The urgency of the problem being addressed is determined by the need to justify the use of biological methods of plant protection in order to reduce the negative im- pact of chemicals and improve human health and environmental safety of domestic products. The prospects of the use of biological plant protection in the agricultural sector.